Peta Konsep Pembelajaran Aqidah Akhlak - Misnan (Hikmah, 2018)
The word morals comes from the Arabic plural khulq which means manners, mannerisms, habits or behaviour. By the term moral science experts are considered not yet right, then according to the more precise they are according to Al Ghazali in the team project the construction of the religion of Islam. So the nature of the learning of aqidah morals is what exactly the essence or foundation of beliefs and behavior (which is based on the inner shape) that good according to Islamic teachings and how human or process to learn it, so that the human understanding teaching well. For terms commonly used term, aqeedah Unity, the science of Kalam, the science of Usul, Theology, mentioning other types of science of kalam i.e. aqa'id Science (i.e. Science creed-creed i.e. node-node/belief, science of Tawhid (the science of keMaha Esaan (God) , and the science of Usul al-Din (i.e. the science of Usul trees religion). For terms commonly used term Shari'a fiqh, worship, muamalah, and moral terms for the commonly used term, tasauf and others. To develop material aqidah morals, then we need to know the magnitude of what material, what part of what's next. Or also called the structure of matter such as we learn about the material of gratitude, we know that it is commendable to God, morals "Backbiting" deplorable morals to sesam is a human, for example: the name of the Angel, Angel, why ugas harusa believers to the Angel, what dampaik is positive if we are faithful to the Angel, how can I do a faith in angels in everyday kehdupan, what is the argumentation to the Angel of faith and so on. So for example we already know, that the material of the faith to this Angel, it's been talked about since the classes in elementary, junior high, when we teach High School or a Student MA and to do it well we teach?, certainly not In learning this the morals of aqeedah the development of the material can be seen in a textual means to develop the core subject matter through literartur or other library resources, and the development of materials tailored to the everyday life of students and this is termed contextual.